PENGARUH GOOD CORPORATE GOVERNANCE(GCG) TERHADAP KEBIJAKAN DIVIDEN PADA SAHAM PERUSAHAAN SEKTOR NON-KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Kania Ester Gunawan; Werner Ria Murhadi; Arif Herlambang (CALYPTRA, 2018)
This study aims to investigate the determinants of corporate dividend policy such as GCG Index, firm size, profitability, leverage, firm growth and free cash flow of companies’ listed in the Indonesian Stock Exchange. This Study uses the quantitative approach and multiple linear reggresion to analyze the data. The target populations of this study are all non-financial companies registered in Indonesia Stock Exchange in 2012-2016 which are equal to 1550 observations. The dependent variable used in this study is corporate dividend policy that measured by using dividend payout ratio. The study finds that firm size, profitability and Leverage affect dividend payout ratio negatively. On the other hand, GCG Index, Firm Growth and Free Cash Flow affect dividend payout ratio positively.